Analisis HOTS dalam soal penilaian akhir semester gasal mata pelajaran matematika kelas IV sekolah dasar - Sandhika Viestra Melania; Sukarno Sukarno; Siti Wahyuningsih (Universitas Sebelas Maret, 2023)
Abstract. The results of the PISA (Program for International Student Assessment) show that the cognitive abilities of Indonesian students are ranked low. Cognitive abilities in mathematics can be improved on condition that students must have higher order thinking skills (HOTS). Therefore, the government has made an educational assessment model in Indonesia directed towards the HOTS assessment model, one of which is in the Final Semester Assessment (FSA). Based on these problems, this study aims to describe the Final Semester Assessment questions for math class IV at Dukuhan Kerten Elementary School for the 2022/2023 academic year based on thinking levels, by classifying questions based on Lower Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and Higher Order Thinking Skills (HOTS). There are two instruments in this study, the main instrument which is the researcher, and the supporting instruments in the form of guidelines for analyzing the cognitive level of Final Semester Assessment questions in class IV mathematics. The instrument was compiled based on according to the cognitive levels of Bloom revised by Anderson and Krathwohl. This research found that out of 35 items, there were 13 questions that belonged to the HOTS cognitive level, in addition, 16 questions were dominated by the C3 cognitive level, then 3 questions included the C2 cognitive level, then 3 questions included the C1 cognitive level. In this question, there is also a stimulus in the form of pictures, graphs, and diagrams.Keywordsi: final semester assessment, High Orders Thingking Skills (HOTS), Mathematic